2007
DOI: 10.1177/152692480701700107
|View full text |Cite
|
Sign up to set email alerts
|

Stress among the Family Caregivers of Liver Transplant Recipients

Abstract: Caregiving stress endures after transplantation. Professional intervention is needed to improve caregivers' quality of life and, consequently, that of transplant recipients as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 44 publications
4
34
1
Order By: Relevance
“…Similar to previous studies in dementia and spinal cord injury, our study found a relatively scant social support in caregivers, which was in turn correlated with depression in these individuals (33,34). Both burden questionnaires, in turn were related to depression and social support, which replicate findings in other chronic diseases (2628). Our study also confirmed findings noted in other diseases, such as mild cognitive impairment in Alzheimer's disease, major depression, Parkinson's disease, and stroke, that the degree of caregiver burden is highly correlated with the patient's cognitive impairment (3538).…”
Section: Discussionsupporting
confidence: 80%
“…Similar to previous studies in dementia and spinal cord injury, our study found a relatively scant social support in caregivers, which was in turn correlated with depression in these individuals (33,34). Both burden questionnaires, in turn were related to depression and social support, which replicate findings in other chronic diseases (2628). Our study also confirmed findings noted in other diseases, such as mild cognitive impairment in Alzheimer's disease, major depression, Parkinson's disease, and stroke, that the degree of caregiver burden is highly correlated with the patient's cognitive impairment (3538).…”
Section: Discussionsupporting
confidence: 80%
“…The study by Cohen et al . was the first study in this area and took the form of a cross‐sectional survey, using the Caregiver Stress Questionnaire, of 24 care‐givers carried out from 1 to 15 years following LT. Their objective was to determine psychological distress amongst caregivers following LT and hypothesized there may be differences between the sexes.…”
Section: Resultsmentioning
confidence: 99%
“…48 Caregiver strain and burden, too, may reduce the quality and effectiveness of the support provided and, indirectly, may increase rates of medication nonadherence. 49,50 …”
Section: Discussionmentioning
confidence: 99%